Growth and economic performance of kid production under different rearing systems and slaughter ages in arid areas of Argentina - Paez Lama, Sebastián Antonio (2013)
This paper evaluated the growth performance of Criollo kids under three different rearing systems and determine the economic profit of each rearing systems with slaughter at two different ages. Forty-eight kids were distributed randomly into three groups (n=16). Two groups of kids were naturally reared with their mothers, suckling goat milk until weaning at 30 and 45days of age (groups N30 and N45, respectively). In the remaining group, kids were artificially reared on milk replacer until 45days of age (group A45). Between 30 and 90days, all groups were ad libitum offered with a ration of alfalfa hay and ground corn. Kids from each group were slaughtered at 60 (n=8) and 90 (n=8) days old. The growth performance of kids was acceptable achieving average daily gain (ADG) values ranging between 115.9 and 129.5gd-1, with no major differences between rearing systems at the end of the study. The natural rearing systems showed low values of gross return, which ranged from -0.60 to 5.67US$kid-1, while the artificial rearing system was not economically viable due to the high cost of milk replacer and high demand of labor. The price of milk replacer should not exceed 20% of meat value so that artificial rearing becomes economically feasible. The average gross return of the two natural rearing groups slaughtered at 90days (3.96±1.46US$kid-1) was three times higher than the animals slaughtered at 60days (1.25±0.93US$kid-1). On the basis of the economic results it would be advisable to raise the kids naturally with goat milk and increase the age of slaugther, as long as consumers accept these older animals without decreasing the selling price of meat.